Dominance and monophthongization: method versus insight - Kortlandt, Frederik (Baltistica, 2012)
The establishment of dominance patterns does not automatically yield insights into the history of accentual paradigms. As in the case of segmental features, it is necessary first to identify the results of analogical developments and to separate them from the original regularities. Both apophony and metatony became highly productive in Latvian and Lithuanian word formation, leading to complex morphonological relationships.